Pengukuran Kepuasan Pengguna Situs Web Jaringan Dokumentasi Dan Informasi Hukum (JDIH) Dengan Metode End User Computing Satisfaction (EUCS - Wenty Ratna Juwita; Khairil Khairil; Indra Kanedi (Jurnal Media Infotama, 2026)
Application for measuring user satisfaction of the Legal Documentation and Information Network website (JDIH) Using the End User Computing Satisfaction (EUCS) method, it can assist the National Legal Documentation and Information Network in measuring the satisfaction of users of the Legal Documentation and Information Network (JDIH) website and can identify and understand the use of the End User Computing Satisfaction (EUCS) method in measuring the satisfaction of users of the Legal Documentation and Information Network (JDIH) website. In applying the End User Computing Satisfaction (EUCS) method to measure the satisfaction level of JDIH website users, a web-based application was developed using the PHP programming language and MySQL database, which can be accessed online via the internet at https://kepuasanpengguna-jdih-bengkulutengahkab.online/. Based on testing using the black box method, the results show that the functionality of the application for measuring user satisfaction with the Legal Documentation and Information Network (JDIH) website has performed as expected and can analyze satisfaction ratings to obtain measurement results for the level of user satisfaction with the Legal Documentation and Information Network (JDIH) website.